A case of beak injuries in chicks of the Raza Espanola Canary caused by a parent during rearing - Ledwoń, Aleksandra; Szanser, Maciej; Adamczyk, Krzysztof; Szeleszczuk, Piotr (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In four 12-13-day-old chicks of the Raza Espanola Canary, partial amputation of beaks by the male that fed the chicks was observed. The chicks were in a good nutrition condition. The mating couple had already reared one clutch in the same season without complications. The young were separated and reared manually. Despite the deformation, the birds are able to feed autonomously. The most likely cause of the parent`s aggressive behaviour is stress associated with high intensity of rearing and a nervous disposition of the male.
Keywords: parental aggression; beak mutilation; canary; Raza Espanola